PERAN LINGKUNGAN KERJA FISIK DALAM MENDORONG KINERJA KARYAWAN: STUDI KUALITATIF PADA BRILLIANT BRAIN INDONESIA MENGGUNAKAN TOOL FOR OBSERVING WORKSITE ENVIRONMENTS (TOWE) - Injilia Wulan Gratia Wua; Fitayantri Tamau; Lidya Djuwita Pratiwi Canon (ITB AAS Indonesia Surakarta, 2026)
This study aimed to examine the role of the physical work environment in enhancing tutor performance at Brilliant Brain Indonesia. A descriptive qualitative approach was employed, using in-depth interviews and observations based on the Tool for Observing Worksite Environments (TOWE). The participants consisted of seven tutors from four branches of Brilliant Brain Indonesia. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicated that most tutors perceived the physical work environment as generally comfortable and supportive of teaching performance. However, several limitations were identified, including physical fatigue caused by non-ergonomic furniture, suboptimal temperature and lighting conditions in certain situations, the absence of safety equipment and informational posters, and the lack of meeting rooms across all branches. These findings suggested a gap between tutors’ subjective perceptions and the objective conditions of the physical work environment. This study was limited by the small number of participants and its focus on a single organization. Nevertheless, this research contributed original value by integrating qualitative interviews with the TOWE instrument to provide a contextual and comprehensive understanding of the role of the physical work environment in supporting tutor performance. Keywords : work environment, physical environment, employee performance, qualitative study, TOWE